Nonlinear switching in silicon-based ring resonators - Kusalajeerung, Channarong; Chiangga, Surasak; Pitukwongsaporn, Santad; Yupapin, Preecha P. (My University, 2011)
In this paper, we analyzed and investigated the nonlinear switching characteristics of an optical device using a double-coupler silicon ring resonator in the presence of the linear losses, the Kerr nonlinearity, two-photon absorption, thermo-optic effects, free-carrier-induced absorption, and dispersion. Results obtained have shown that the general features of the nonlinear switching of the throughput and drop port signals are similar to a single-couple ring and nonlinear Fabry-Perot resonators, respectively. The interesting results of the double-coupler silicon ring resonator are the low switching power conditions and the linear amplification gain. The various applications can be provided by controlling the input-output of silicon-based resonators, for instance, by controlling the coupling ratio, free-carrier lifetime, and input wavelength, in which the multiple applications for optical switches, logic gates, and memories can be provided. © 2011 Society of Photo-Optical Instrumentation Engineers (SPIE).
Keywords: integrated optics; nonlinear switching; optical bistability; ring resonator